Unusual Case of External Juxta Coronal Odontoma - Fatemeh Dehghani Nazhvani; Ali Azadikhah; Tayebeh Dorudizadeh; Pardis Haddadi; Ali Dehghani Nazhvani; Nafiseh Shamloo (Shiraz University of Medical Sciences, 2021)
Odontomas are benign tumors of jaws with mixed tissue, which are the result of proliferation of odontogenic epithelium and mesenchymal cells. They occur almost centrally and seldom peripherally. There is no report of such a lesion externally while attaching a tooth crown. In this case, we present a lesion on the buccal surface of the right maxillary central incisor crown, which is misconstrued with a dental overgrowth. Such cases may confuse diagnosis during clinical examination. Radiographically, such odontomas may be mistaken for various other lesions. Ultimate diagnosis should be relied upon microscopic evaluation and histopathological results.